Organizational and economic mechanism for implementing the functions of state strategic controlling at industrial enterprises - E. A. Sorokin (Путеводитель предпринимателя)
The prerequisites for increasing the role of public administration in organizing the production of special–purpose products based on the use of state strategic controlling are considered. An organizational and economic mechanism for the implementation of the functions of state strategic controlling at industrial enterprises is proposed, which is characterized by the integration of controlling functions in industry and the state acceptance system and involves the introduction of an integrated organizational structure of controlling.